Clinical advances in kidney autotransplantation: a review - Shengjie Lin; Jingci Gai; Shangjin Huang; Yingzhen He; Da Hao; Shuhang Luo; Yilong Lin; Jiang Qiu; Jun Li; Changxi Wang; Chenglin Wu (BMC Surgery)
Abstract Kidney autotransplantation is a surgical procedure with multiple indications and advancing technological approaches. Kidney autotransplantation is used to address complex kidney-related diseases including renal vascular lesions, ureteral diseases, tumors, loin pain-hematuria syndrome, and conditions affecting a solitary kidney or both kidneys. Renal artery lesions, including aneurysms and stenoses, often necessitate kidney autotransplantation in cases involving renal artery bifurcation or distant failure of endovascular repair. Complex ureteral lesions such as ureteral avulsions are commonly treated with kidney autotransplantation. Renal tumors, especially centrally located tumors or those involving the renal hilum, are treated using this technique while preserving renal function. It is worth emphasizing that this would be a rarely used last-resort technique in the modern era of minimally invasive nephron-sparing surgery. Kidney autotransplantation may be indicated for the rare condition of loin pain-hematuria syndrome when conservative measures fail. Additionally, individuals with solitary or bilateral kidney disease benefit from kidney autotransplantation to preserve their renal function. Traditional open-kidney autotransplantation involves renal extraction, workbench repair, and renal reimplantation. Technological advancements have introduced minimally invasive techniques including laparoscopic- and robot-assisted kidney autotransplantation, which reduce surgical trauma and recovery times. These techniques have shown promising outcomes, and robotic platforms have the potential to further reduce complications. In this study, we reviewed diverse indications and recent technological innovations in the field of kidney autotransplantation.